Italy's Decline: A Political Economy Perspective. (22nd July 2022) - Guardiancich, Igor
Abstract : International observers have not been kind to Italy during the past two decades. The International Monetary Fund (IMF, 2016 ) wrote about the country's two lost decades, the Economist (19 May 2005 ) described it as the real sick man of Europe and eminent economists, such as Bruno Pellegrino and Luigi Zingales (Pellegrino and Zingales, 2017 ), tried to diagnose the Italian disease. Italy's GDP has barely grown since the mid-1990s and the past decade was the worst in the history of its economy, world wars included.